The Influence of Discounts & Free Shipping on Purchase Decisions through the Buying Interest of Universitas Negeri Jakarta Students on Shopee - Nirmala Fauziah; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
The primary objective of this investigation is to analyze how promotional incentives, specifically price discounts and free shipping, influence the actual purchasing choices of Universitas Negeri Jakarta (UNJ) students on Shopee, with purchase intention acting as a mediating factor. Using an explanatory quantitative framework, primary data were gathered from 114 active Shopee users through purposive sampling. The analytical process in this study employed Structural Equation Modeling using the Partial Least Squares technique to examine the relationships among variables. The empirical findings indicate that both price discounts and free shipping programs exert a substantial positive impact on purchase intention. However, these promotional tools do not demonstrate a significant direct effect on the final purchase decision. Instead, purchase intention serves as a critical bridge, fully mediating the relationship between marketing stimuli and transaction behavior. It is concluded that while external incentives attract attention, the actual conversion into a sale depends heavily on the consumer's psychological intent. These results imply that e-commerce platforms should prioritize strategies that nurture consumer interest and desire rather than relying solely on cost reduction. Effective marketing for the student demographic must bridge the gap between initial attraction and the internal commitment to buy.